IDENTIFIKASI KEBERADAAN BAKTERI PADA SAMBAL LALAPAN DI CIGOMBONG KOTARAJA PAPUA - Taroreh, Jannete Elisabeth; Romadhonni, Tika; Rampa, Ester; Sinaga, Herlando (Universitas Cokroaminoto Palopo, 2023)
Research has been carried out with the title Identification of the Presence of Bacteria in Sambal Lalapan in Cigombong Kotaraja at the Biology Laboratory of Cenderawasih University Jayapura using samples of sambal lalapan. This research was conducted for 3 months starting from April 23, 2022 to June 6, 2022. The purpose of this study was to determine the presence of bacteria in sambal lalapan in Cigombong Kotaraja. The type of research used in this study is descriptive with a laboratory approach to identify the presence or absence of bacteria in chili sauce in Cigombong Kotaraja. The population used in this study were all fresh chili sauce sellers in Cigombong Kotaraja. The number of samples in this study were 5 samples (total population). The research method used is descriptive method by means of microscopy. To determine the presence or absence of bacteria in sambal lalapan in Cigombong Kotaraja, analyzed by Colony Counter and Microscope by planting on Sodium Agar (NA) media and Gram staining and obtained the results of 5 samples (100%) of sambal lalapan all positive for bacterial contamination with Bacil bacterial cell shape, Gram Negative, Red in color.